Comparative genomics of vesicomyid clam (Bivalvia: Mollusca) chemosynthetic symbionts - Newton, Irene LG (BioMed Central, 2008)
BACKGROUND: The Vesicomyidae (Bivalvia: Mollusca) are a family of clams that form symbioses with chemosynthetic gamma-proteobacteria. They exist in environments such as hydrothermal vents and cold seeps and have a reduced gut and feeding groove, indicating a large dependence on their endosymbionts for nutrition. Recently, two vesicomyid symbiont genomes were sequenced, illuminating the possible nutritional contributions of the symbiont to the host and making genome-wide evolutionary analyses possible. RESULTS: To examine the genomic evolution of the vesicomyid symbionts, a comparative genomics framework, including the existing genomic data combined with heterologous microarray hybridization results, was used to analyze conserved gene content in four vesicomyid symbiont genomes. These four symbionts were chosen to include a broad phylogenetic sampling of the vesicomyid symbionts and represent distinct chemosynthetic environments: cold seeps and hydrothermal vents. CONCLUSION: The results of this comparative genomics analysis emphasize the importance of the symbionts' chemoautotrophic metabolism within their hosts. The fact that these symbionts appear to be metabolically capable autotrophs underscores the extent to which the host depends on them for nutrition and reveals the key to invertebrate colonization of these challenging environments.